Toxic epidermal necrolysis induced by COVID-19 - Duaa Alahmadi; Azhar Ahmed; Walaa Borhan; Ahmad Ozbuck; Esraa Shaheen (PAGEPress Publications, 2024)
Toxic epidermal necrolysis (TEN) is a life-threatening acute mucocutaneous syndrome. It is characterized by keratinocyte necrosis and apoptosis, which affect more than 30% of the body's surface. TEN is most commonly due to an altered immunological response to specific drugs, infections, and malignancies, or it can be idiopathic. The combination of TEN and COVID-19 can have a fatal outcome if not recognized and promptly treated. Therefore, fast reporting of such cases will draw doctors' attention to quick and right intervention. In this article, we present a 66-year-old patient with a clinical presentation of toxic epidermal necrolysis along with a coexisting COVID-19 infection. To our knowledge, this is the first case of TEN in a patient diagnosed with SARS CoV‑2 infection in Saudi Arabia.